2014
DOI: 10.1002/mbo3.198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the minimal replicon and the origin of replication of the crenarchaeal plasmid pRN1

Abstract: We have determined the minimal replicon of the crenarchaeal plasmid pRN1. It consists of 3097 base pairs amounting to 58% of the genome of pRN1. The minimal replicon comprises replication operon orf56/orf904 coding for a transcriptional repressor and the replication protein of pRN1. An upstream region of 64 bp that contains the promoter of the replication operon is essential as well as 166 bp of sequence downstream of the orf904 gene. This region contains a putative transcriptional terminator and a 100 nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For cloning of pSVAmZ-SH10 the minimal replicon of pRN1 consisting of the region surrounding orf56 and orf904 was shortened and the remaining NdeI site simultaneously removed 47 . To this end, two backbone fragments were amplified using the primer combinations mod_Size_fw, mod_NdeI_del_rev and mod_NdeI_del_fw, mod_Size_rev and assembled by overlap PCR.…”
Section: Methodsmentioning
confidence: 99%
“…For cloning of pSVAmZ-SH10 the minimal replicon of pRN1 consisting of the region surrounding orf56 and orf904 was shortened and the remaining NdeI site simultaneously removed 47 . To this end, two backbone fragments were amplified using the primer combinations mod_Size_fw, mod_NdeI_del_rev and mod_NdeI_del_fw, mod_Size_rev and assembled by overlap PCR.…”
Section: Methodsmentioning
confidence: 99%
“…All family members share a conserved genomic region and three highly conserved gene products which have been characterised biochemically (Peng et al, 2000). Recent studies have revealed that a single multifunctional replication protein (ORF904) with helicase, primase and DNA polymerase activity, reminiscent of the type of replication performed by some linear bacteriophages, is required to initiate plasmid replication (Lipps, 2011;Berkner et al, 2014 marked contrast to all DNA polymerases, ORF904 is able to polymerise DNA de novo, i.e. without a primer.…”
Section: Small Cryptic Plasmidsmentioning
confidence: 99%
“…However, unlike conventional AEP members that function as replication initiation-specific primases, PrimPols play diverse roles in different organisms (Guilliam et al, 2015). For example, PrimPol from archaeal plasmid pRN1 (ORF904) is suggested to be a replicative DNA polymerase (Berkner et al, 2014), while human PrimPol (hPrimPol) is involved in DNA damage tolerance (Bianchi et al, 2013;García-Gómez et al, 2013). Recently, it is reported that a PrimPol encoded in a mobile element of Thermus thermophilus is contributed in defense against invading DNA (García-Quintans et al, 2020).…”
Section: Introductionmentioning
confidence: 99%